Autism in the Context of Humanitarian Emergency: The Lived Experiences of Syrian Refugee Mothers of Children on the Autism Spectrum - Bernier, Abdullah; McCrimmon, Adam; Nsair, Sumaya; Hans, Henna (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2023)
This study explored the resettlement experiences of Syrian refugees accessing supports and services for their autistic children in Alberta, Canada. Using interpretive phenomenological analysis (IPA), in-depth interviews with three participants led to seven shared themes regarding parental experiences with the Syrian crisis, access to supports and services, barriers to resettlement, and sentiments regarding their resettlement. Findings are explained using migrant adaptation models to situate practice within a social justice orientation by understanding the perspectives of vulnerable migrant populations. Practical implications include ways to benefit refugees, imbue culture within practice, inform policy initiatives, and highlight the importance of trauma-informed care.